1993
DOI: 10.1002/jez.1402650417
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal conditions determine the manner of skin rejection in reptiles

Abstract: During summer, 33%,52%, and 15% of lizards Chalcides ocellatus rejected first set skin allografts (time between day of first sign of rejection and end point), respectively in an acute (11)(12)(13)(14) days), subacute (15-20 days), and chronic (21)(22)(23)(24) days) manner. Second set grafts were rejected in an acute fashion (8)(9)(10)(11)(12)(13) Several reports have documented that different reptilian species reject skin allotransplants in a typically chronic fashion (Maslin, '67; Manickavel and Muthukkarup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Afifi et al found a seasonal pattern in the ability of the ocellated skink (Chalcides ocellatus) to reject skin grafts (Afifi et al, 1993). The timing of the onset of rejection was longest in the winter, with rejection delayed until the following spring.…”
Section: Cell-mediated Immunitymentioning
confidence: 99%
“…Afifi et al found a seasonal pattern in the ability of the ocellated skink (Chalcides ocellatus) to reject skin grafts (Afifi et al, 1993). The timing of the onset of rejection was longest in the winter, with rejection delayed until the following spring.…”
Section: Cell-mediated Immunitymentioning
confidence: 99%
“…The functional role of granulocytes and monocytes in reptilian immune systems is almost unknown, although their presence suggests relative importance (Cooper et ai., 1985). Evidence for a major histocompatibility complex (MHC) in ectotherms is largely based upon functional studies such as allograft rejection (Afifi et al, 1993) and mixed leucocyte reaction (Saad et al, 1986). Reptiles synthesize at least two classes of immunoglobulin (Ig): a high molecular weight Ig related to mammalian IgM, and a more distantly related Ig, termed IgY, of lower molecular weight (EI Ridi, 1992).…”
Section: Cell Typesmentioning
confidence: 99%
“…Periodic seasonal changes have influenced all life forms, as exemplified by seasonal physiology and behaviours across plant and animal species 1 2 3 . For example, reptile graft rejection 4 and level of gonadal hormones in squirrel monkeys 5 display seasonal variation. In humans, many complex polygenic diseases, including cardiovascular 6 7 , autoimmune 8 9 and psychiatric illnesses 10 11 12 , have established seasonal patterns of incidence and disease activity.…”
mentioning
confidence: 99%